CASP6 predicts poor prognosis in glioma and correlates with tumor immune microenvironment - Guo, Kai; Zhao, Jiahui; Jin, Qianxu; Yan, Hongshan; Shi, Yunpeng; Zhao, Zongmao (Frontiers in Oncology, 2022)
Background: Glioma is an aggressive tumor of the central nervous system. Caspase-6 (CASP6) plays a crucial role in cell pyroptosis and is a central protein involved in many cellular signaling pathways. However, the association between CASP6 and prognosis of glioma patients remains unclear. Methods: Four bioinformatic databases were analyzed to identify differentially expressed genes (DEGs) between glioma and healthy tissues. Eighty-one protein-coding pyroptosis-related genes (PRGs) were obtained from the GeneCards database. The pyroptosis-related DEGs (PRDEGs) were extracted from each dataset, and CASP6 was found to be aberrantly expressed in glioma. We then investigated the biological functions of CASP6 and the relationship between CASP6 expression and the tumor microenvironment and immunocyte infiltration. The half maximal inhibitory concentration of temozolomide and the response to immune checkpoint blockade in the high- and low-CASP6 expression groups were estimated using relevant bioinformatic algorithms. Quantitative real-time reverse transcription PCR and western blotting were carried out to confirm the different expression levels of CASP6 between human astrocytes and glioma cell lines (U251 and T98G). We determined the role of CASP6 in the tumorigenesis of glioma by knocking down CASP6 in U251 and T98G cell lines. Results: We found that CASP6 was overexpressed in glioma samples and in glioma cell lines. CASP6 expression in patients with glioma correlated negatively with overall survival. In addition, CASP6 expression correlated positively with the degree of glioma progression. Functional analysis indicated that CASP6 was primarily involved in the immune response and antigen processing and presentation. Patients with high CASP6 levels responded more favorably to temozolomide, while patients with low expression of CASP6 had a better response to immunotherapy. Finally, in vitro experiments showed that CASP6 knockdown inhibited glioma proliferation. Conclusions:The pyroptosis-related gene CASP6 might represent a sensitive prognostic marker for patients with glioma and might predict their response of immunotherapy and temozolomide therapy. Our results might lead to more precise immunotherapeutic strategies for patients with glioma.